2020
DOI: 10.1039/d0tc02351e
|View full text |Cite
|
Sign up to set email alerts
|

A zero-dimensional hybrid lead perovskite with highly efficient blue-violet light emission

Abstract: Pursuit of high-performance blue light emitting perovskite have attracted intensive attention due to insufficient photoluminescence quantum yield (PLQY) of <5% for CsPbCl3, which far lag behind the near-unit PLQYs (>90%)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Lei et al. reported [PbCl 6 ] 4− unit‐based blue‐violet emissive 0D hybrid [BAPrEDA]PbCl 6 (H 2 O) 2 , with small Stokes shift and high PLQY (∼21 %) as shown in Figure 5a and Figure 5b [31] . Recently, Bolink et al.…”
Section: One‐ and Zero‐dimensional (1d And 0d) Metal Halide Hybridsmentioning
confidence: 95%
See 1 more Smart Citation
“…Lei et al. reported [PbCl 6 ] 4− unit‐based blue‐violet emissive 0D hybrid [BAPrEDA]PbCl 6 (H 2 O) 2 , with small Stokes shift and high PLQY (∼21 %) as shown in Figure 5a and Figure 5b [31] . Recently, Bolink et al.…”
Section: One‐ and Zero‐dimensional (1d And 0d) Metal Halide Hybridsmentioning
confidence: 95%
“…with small Stokes shift and high PLQY (~21 %) as shown in Figure 5a and Figure 5b. [31] Recently, Bolink et al reported 0D mixed-halide hybrid MA 4 PbX 6 • 2H 2 O (MA=[CH 3 NH 3 ] + ; X=Br 1-x I x with 0 < × < 1) that can undergo reversible transformation to 3D MAPbX 3 phase when thermally annealed. [32] Seesaw structured 0D Pb hybrids (C 13 H 19 N 4 ) 2 PbBr 4 and (Bmpip) 2 PbBr 4 both emit blue light under UV excitation with relatively small Stokes shift.…”
Section: S 2 Based 0d Hybrids (Pb 2 + Bi 3 + )mentioning
confidence: 99%
“…For example, Zhou et al synthesized a 0D metal halide of (C 9 NH 20 ) 7 (PbCl 4 )Pb 3 Cl 11 with blue emission band at 470 nm excited by 350 nm UV light sources, and a Stokes shift of 120 nm [16]. Sun et al reported a 0D metal halide of [BAPrEDA]PbCl 6 •(H 2 O) 2 with broadband blue emission peaking at 392 nm excited by 300 nm UV light sources and a Stokes shift of 90 nm [17]. However, in order to obtain 0D metal halides with blue emission, the excitation wavelength needs to have higher energy and the excitation peak is generally less than 350 nm, which is affected by the large Stokes shift of 0D metal halide.…”
Section: Introductionmentioning
confidence: 99%
“…reported the highest efficient blue‐violet (392 nm) light emission of 0D [BAPrEDA]PbCl 6 ·(H 2 O) 2 with a PL QY of 21.3%, which far exceeds than that of the typical 3D CsPbCl 3 (<5%). [ 66 ] The enhancement of PL QY for the 0D perovskite was attributed to the strong quantum confinement effect of the 0D structure and highly localized electron in isolated [PbCl 6 ] 4− octahedrons. Typical quantum dots with quantum confinement effect have been demonstrated to show markedly decreased PL QY when they are made into solid form, [ 67 ] but the 0D perovskite Cs 4 PbBr 6 solids still maintain high PL QY.…”
Section: Properties Of 0d Perovskitesmentioning
confidence: 99%
“…[ 28a ] The high PL QY in 0D perovskites was due to their dramatically increased exciton binding energy that had been confirmed to be derived from their strong quantum confinement. [ 66 ] Despite 0D perovskites exhibit excellent PL properties, PL regulation/optimization is still of vital importance for these materials to realize commercialization In general, the PL properties can be easily regulated by changing the chemical compositions and the synthetic temperature. Some representative researches on the PL regulation of 0D perovskites in the past several years are discussed below.…”
Section: Properties Of 0d Perovskitesmentioning
confidence: 99%